MANAGING LEAD TIME VARIABILITY IN THE ACTIVITY INGREDIENT SUPPLY CHAIN: A GAME THEORY-BASED RISK RESPONSE FRAMEWORK - Tramarico, Claudemir Leif [UNESP] (My University, 2024)
Uncertainty and disruption can significantly impact supply chains, and risk response is a means to diminish or circumvent these challenges. Therefore, this investigation aims to assess lead time variability in the supply chain of active ingredients. The research proposes a decision-making process to evaluate lead time variability in the active ingredient supply chain of the Brazilian chemical industry. It adopts Game Theory and linear programming in its solution. The two major contributions of this study are as follows: first, it presents a procedure to assess lead time variability; second, it proposes a supply chain risk response framework to address the lead time variability problem. Supply chain and lead time variability are emerging areas that offer significant opportunities for exploration, one of which is to evaluate lead time variability from the multiple perspectives presented in this study, thereby contributing to the current literature through a real application.
Keywords: decision-making process; lead time variability; supply chain risk